White Matter Plasticity in Reading-Related Pathways Differs in Children Born Preterm and at Term: A Longitudinal Analysis - Bruckert, Lisa; Borchers, Lauren R.; Dodson, Cory K.; Marchman, Virginia A.; Travis, Katherine E.; Ben-Shachar, Michal; Feldman, Heidi M. (Frontiers in Human Neuroscience, 2019)
Children born preterm (PT) are at risk for white matter injuries based on complications of prematurity. They learn to read but on average perform below peers born full term (FT). Studies have yet to establish whether properties of white matter pathways at the onset of learning to read are associated with individual variation later in reading development in PT children. Here, we asked whether fractional anisotropy (FA) at age 6y is associated with reading outcome at age 8y in PT children in the same pathways as we previously demonstrated in a sample of FT children (Borchers et al., 2018). PT (n = 34, mean gestational age = 29.5 weeks) and FT children (n = 37) completed diffusion MRI and standardized measures of non-verbal IQ, language, and phonological awareness at age 6y. Reading skills were assessed at age 8y. Mean tract-FA was extracted from pathways that predicted reading outcome in children born FT: left arcuate fasciculus (Arc), bilateral superior longitudinal fasciculus (SLF), and left inferior cerebellar peduncle (ICP). We explored associations in additional pathways in the PT children: bilateral inferior longitudinal fasciculus (ILF) and uncinate fasciculus (UF). Linear regression models examined whether the prediction of reading outcome at age 8y from mean tract-FA at age 6y was moderated by birth group. Children born PT and FT did not differ significantly in tract-FA at age 6y or in reading at age 8y. Sex, socioeconomic status and non-verbal IQ at age 6y were associated with reading outcome and were included as covariates in all models. Birth group status significantly moderated associations between reading outcome and mean tract-FA only in the left Arc, right SLF, and left ICP, before and after consideration of pre-literacy skills. Microstructural properties of these cerebral and cerebellar pathways predicted later reading outcome in FT but not in PT children. Children born PT may rely on alternative pathways to achieve fluent reading. These findings have implications for plasticity of neural organization after early white matter injury.